2018
DOI: 10.1007/978-3-030-03667-6_31
|View full text |Cite
|
Sign up to set email alerts
|

Using SPARQL – The Practitioners’ Viewpoint

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…They report that 71% of their respondents used property paths. Similarly to Bonifati et al [6], Warren and Mulholland [7] found that /, * and | were relatively frequently used operators. They also found that one or more (+) was relatively frequently used, and that ^ and ?…”
Section: Related Workmentioning
confidence: 69%
See 1 more Smart Citation
“…They report that 71% of their respondents used property paths. Similarly to Bonifati et al [6], Warren and Mulholland [7] found that /, * and | were relatively frequently used operators. They also found that one or more (+) was relatively frequently used, and that ^ and ?…”
Section: Related Workmentioning
confidence: 69%
“…), disjunction (|), zero or more (*) and concatenation (/) were relatively frequently used. Complementing these studies, Warren and Mulholland [7] have surveyed the usage of SPARQL1.1 features. They report that 71% of their respondents used property paths.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, our approach leads to a more sustainable codebase. To give evidence of this statement, we use the tool cloc 20 to count the lines of Java code required to implement the core module of SPARQL Generate in Apache Jena (without considering format-specific extensions 21 ) and the RML implementation in Java 22 . SPARQL Generate and RML require developing and maintaining 12280 and 7951 lines of Java code, respectively.…”
Section: Requirements Satisfaction and Discussionmentioning
confidence: 99%
“…Many SPARQL users fall into the category of end-user developer. In a survey of SPARQL users, [22] found that although 58% came from the computer science and IT domain, other SPARQL users came from non-IT areas, including social sciences and the humanities. Findings in this area [19] suggest that the data with which users work is more often primarily list-based and/or hierarchical rather than tabular.…”
Section: Related Workmentioning
confidence: 99%
“…Однако набор поддерживаемых возможностей обычно значительно меньше, чем в SPARQL. Например, редактор RDF Explorer [4] поддерживает составление запросов, состоящих только из основного графового шаблона запроса 3 , где концепты могут быть заменены переменными. Авторы работы позиционируют RDF Explorer как редактор для пользователей, не являющихся экспертами.…”
Section: обзор редакторов Sparql-запросовunclassified